Characterizing the control logic of web applications’ user interfaces - Silva, Carlos Eduardo (2014)
In order to develop an hybrid approach to the Reverse Engineer of Web applications, we need first to understand how much of the control logic of the user interface can be obtained from the analysis of event listeners. To that end, we have developed a tool that enables us to perform such analysis, and applied it to the implementation of the one thousand most widely used Websites (according to Alexa Top Sites). This paper describes our approach for analyzing the user interface layer of those Websites, and the results we got from the analysis. The conclusions drawn from the exercise will be used to guide the development of the proposed hybrid reverse engineering tool.